The Potential Role of Urinary Microbiota in Bladder Carcinogenesis: A Systematic Review - Ghabousian, Amir; Shafigh, Ashkan; Tayebi, Sona; Salehi-Pourmehr, Hanieh; Mostafaei, Hadi; Lemberger, Ursula; Mori, Keiichiro; Sadeghi-Ghyassi, Fatemeh; Hassanzadeh, Hoora; Hajebrahimi, Sakineh; et al. (Urology Journal, 2024)
Purpose: The quantitative objective of the current systematic review was to identify the potential role of urinary microbiota in bladder cancer (BC) carcinogenesis, invasiveness, progression, and metastasis. Materials and Methods: The proposed systematic review was conducted in accordance with critical review according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, and the Joanna Briggs Institute (JBI) methodology for systematic reviews. The search strategy aimed to find both published and unpublished studies up to the January 2024. A JBI appraisal checklist was used to assess possible biases. Results: This systematic review was centered on 27 studies comprising 926 BC patients. Overall, 412 control individuals were compared with BC patients. The most common sampling method was midstream urine collection. Regarding microbial alpha diversity, there was no statistically significant difference between cancerous and healthy samples (n = 8), recurrent and not recurrent (n = 1), responders versus non-responders(n = 1), tumor grades (n = 1), and collection methods (n = 1). However, five studies reported higher diversity in controls, and five other studies reported, conversely, high levels of alpha diversity in BC patients or recurrent cases. Furthermore, a responder (RE) to treatment and a non-muscle invasive bladder cancer (NMIBC) groups demonstrated significant difference with non-responder (NR) and muscle invasive bladder cancer (MIBC), respectively. In terms of beta-diversity, nine studies reported significant diversity between BC patients and controls, one article demonstrated difference between recurrent and not recurrent patients, a study reported significant difference in RE and NR groups whereas another showed opposite, and others (n = 4) did not find any difference between BC, controls, MIBC and NMIBC patients, or between tumor grades. One study reported a difference between the collection method and beta-diversity in males and another reported the difference in females. Conclusion: The included studies demonstrate that the composition of urinary microbiota is altered in patients with BC. However, the differentially enriched genera in the urine of these patients vary between studies, and there is too much heterogeneity across studies to make any reliable and valid conclusions. Furthermore, well-designed research is necessary to assess the role of microbiota in the carcinogenesis and progression of BC.